The relations between leadership and knowledge management - Jada, Shaheer (My University, 2018)
In their aim to gain the competitive edge, organisations are attempting to leverage off of their individual core competencies by turning towards knowledge management practices (KM). By successfully boosting knowledge management practices, organisations believe that this will aid them in increasing their productivity, achieving innovative solutions and achieving a better level of quality for their services and products to customers. Therefore, the contributions that may be brought by KM practices to the overall success of the firm have been extensively recognised. However past research has shown that both leadership behaviours as well as organisational climate are proven barriers to the organisations leveraging and creating knowledge. The existing body of knowledge posits that in order for knowledge management practices to be effective and implemented efficiently, a diagnostic fit needs to be done between the firm and the proposed knowledge management objectives. Therefore, it is critical to establish how leadership styles and organisational climate affect the firm’s capability to apply and create knowledge. Thereafter the firm may focus on relevant strategies that may be used to adjust the climate of the organisation or redesign it in order to support the knowledge management objectives. After critically evaluating the research pertaining to KM and leadership styles research illustrates supporting links. However, research relating to the combination of all three is severely lacking. Therefore, this study will examine this research gap. In precise terms, this study will examine the relationship between KM practices and leadership styles, whilst evaluating the moderating effects of the organisations climate. In order to do this, a conceptual framework will be developed that will compromise of four constructs, namely: transformational leadership, transactional leadership, organisational climate and KM practices. This research study will make use of a post positivist paradigm and will consist of a cross sectional research design. Quantitative data will be collected after evaluating the four main hypotheses in order to conclude if a relationship exists between all three variables. The participants for this study will be from a small and medium sized enterprise within South Africa. It is expected that all three variables bear a positive relationship to each other.
A research report submitted to the faculty of Commerce, Law and Management, University of Witwatersrand, Johannesburg, in fulfillment of the requirements of the degree of Masters Of Commerce by research.
Keywords: Knowledge management; Organizational learning; Industrial management